2007
DOI: 10.1037/1072-5245.14.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of stressful experiences: Depressive symptoms, self-esteem, gender, and coping.

Abstract: Numerous studies have identified depressive symptoms as antecedent to stressful experiences. However, the interrelations of depressive symptoms, personal resources, and coping as antecedents of stressful experiences are largely unknown. For this investigation, a prospective design was used to test a model estimating two categories of daily hassles at Time 2 in relation to depressive symptoms, self-esteem, gender, coping, and daily hassles at Time 1. Utilizing simultaneous equations, direct effects were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 65 publications
0
24
0
3
Order By: Relevance
“…The finding of increased occurrences of future dependent life stressors has been replicated with diagnoses of depression in children and adolescents (Daley et al, 1997; Hammen & Brennan, 2001; Harkness, Lumley & Truss, 2008; Harkness & Stewart, 2009; Rudolph, 2008; Williamson, Birmaher, Anderson, Al-Shabbout & Ryan, 1995), men (Cui & Vaillant, 1997), women (Hammen, Shih & Brennan, 2004), treatment-seeking mothers (Feske et al, 2001), and adult patients (Chun, Cronkite & Moos, 2004; Harkness, Monroe, Simons & Thase, 1999). Similarly, the stress generation effect has been documented with depressive symptomatology in children and adolescents (Clements, Aber & Seidman, 2008; Hankin, Mermelstein & Roesch, 2007; Kercher & Rapee, 2009; Kercher, Rapee & Schniering, 2009; Shih, Abela & Starrs, 2009), college students (Barker, 2007; Gibb, Beevers, Andover & Holleran, 2006; Joiner, Wingate, Gencoz & Gencoz, 2005; Potthoff, Holahan & Joiner, 1995; Shih, 2006), company trainees (Orth, Robins & Meier, 2009), newly-wed women (Davila, Bradbury, Cohan & Tochluk, 1997), adults (Daley, Hammen, Davila & Burge, 1998), older adults (Moos et al, 2005), and ethnic minorities (Wingate & Joiner, 2004). Several of these studies, however, also reported higher rates of independent stressors (Clements et al, 2008; Harkness & Stewart, 2009; Kercher et al, 2009; Moos et al, 2005; Wingate & Joiner, 2004).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The finding of increased occurrences of future dependent life stressors has been replicated with diagnoses of depression in children and adolescents (Daley et al, 1997; Hammen & Brennan, 2001; Harkness, Lumley & Truss, 2008; Harkness & Stewart, 2009; Rudolph, 2008; Williamson, Birmaher, Anderson, Al-Shabbout & Ryan, 1995), men (Cui & Vaillant, 1997), women (Hammen, Shih & Brennan, 2004), treatment-seeking mothers (Feske et al, 2001), and adult patients (Chun, Cronkite & Moos, 2004; Harkness, Monroe, Simons & Thase, 1999). Similarly, the stress generation effect has been documented with depressive symptomatology in children and adolescents (Clements, Aber & Seidman, 2008; Hankin, Mermelstein & Roesch, 2007; Kercher & Rapee, 2009; Kercher, Rapee & Schniering, 2009; Shih, Abela & Starrs, 2009), college students (Barker, 2007; Gibb, Beevers, Andover & Holleran, 2006; Joiner, Wingate, Gencoz & Gencoz, 2005; Potthoff, Holahan & Joiner, 1995; Shih, 2006), company trainees (Orth, Robins & Meier, 2009), newly-wed women (Davila, Bradbury, Cohan & Tochluk, 1997), adults (Daley, Hammen, Davila & Burge, 1998), older adults (Moos et al, 2005), and ethnic minorities (Wingate & Joiner, 2004). Several of these studies, however, also reported higher rates of independent stressors (Clements et al, 2008; Harkness & Stewart, 2009; Kercher et al, 2009; Moos et al, 2005; Wingate & Joiner, 2004).…”
Section: Resultsmentioning
confidence: 92%
“…In a study ( n =1211) focusing exclusively on avoidance coping (Holahan, Moos, Holahan, Brennan & Schutte, 2005), this coping style was prospectively predictive of chronic and episodic dependent stress occurring over a four-year interval. Extending these findings to other coping strategies, Barker (2007; n =241) assessed problem-focused, emotion-focused, and avoidant coping in relation to subsequent interpersonal and academic hassles experienced over a four-week interval. Again, avoidant coping was prospectively associated with interpersonal hassles.…”
Section: Resultsmentioning
confidence: 99%
“…Studies appear to consistently show that females report more chronic stressors related to interpersonal relationships (e.g., friends, relatives, acquaintances in social network) than males (Barker, 2007; Davis, Matthews, & Twamley, 1999; Liu & Alloy, 2010; McIntyre, Korn, & Matsuo, 2008; Shih, Eberhart, Hammen, & Brennan, 2006). A few studies have demonstrated that males experience more work-related and financial chronic stressors than women (Loosemore & Waters, 2004; Young & Korszun, 2010).…”
Section: Gender As a Moderator Of Physiological Responses To Stressmentioning
confidence: 99%
“…Recent works have demonstrated that women experience more stressful life events than men (e.g., Barker, 2007;Davila, Bradbury, Cohan, & Tochluk, 1997;Rudolph & Hammen, 1999;Shih, Eberhart, Hammen, & Brennan, 2006). Moreover, women have been shown to be more reactive to stress than men (Rudolph & Flynn, 2007;Shih et al, 2006) such that women are more likely than men to be depressed in reaction to stressful life events (Kessler & McLeod, 1984;Leadbeater, Blatt, & Quinlan, 1995;Rudolph & Flynn, 2007;Shih et al, 2006).…”
mentioning
confidence: 90%